The Impact of Celebrity Endorsement and Brand Image on Gen Z Purchasing Decisions For Avoskin Products With Brand Awareness as A Mediating Variable - Puan Dwi Yanti; Muhammad Faisal Yul Zamrudi (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This study examines the impact of celebrity endorsement and brand image on Gen Z consumers' purchasing decisions, with brand awareness as a mediating variable. The study focuses on Avoskin cosmetics in Semarang, aiming to understand the factors influencing consumer preferences and purchasing behavior. The research employs a quantitative explanatory approach with a sample of 100 Gen Z respondents. Data were collected through structured questionnaires and analyzed using statistical methods, including multiple linear regression and the Sobel test for mediation. The results indicate that celebrity endorsement positively influences brand awareness, although its impact on purchasing decisions is insignificant. Conversely, brand image significantly affects brand awareness and purchasing decisions. Brand awareness also mediates the relationship between independent variables (celebrity endorsement and brand image) and purchasing decisions, enhancing their overall effect. Brand image and awareness are crucial factors driving consumer purchasing decisions, while celebrity endorsement alone is insufficient without alignment with core product values and consumer expectations. This study highlights the importance of tailored marketing strategies for Gen Z preferences.